O ensino de Matemática na Educação de Jovens e Adultos em uma perspectiva sociocultural - Santos, Vilma Barros Gomes. (2024)
This research addresses the theme of Mathematics Education for Youth and Adults, discussing the enriching relationship between students' prior and sociocultural knowledge and the context of teaching and learning mathematics in school. The present study aims to investigate the mathematical knowledge of students in the Youth and Adult Education (EJA) program and establish connections between this knowledge and school mathematical concepts, focusing on 8th and 9th grade classes, within a sociocultural education framework. The participants of this research are students enrolled in the 4th cycle of Youth and Adult Education (EJA), corresponding to the 8th and 9th grades of elementary school, aged 15 to 19, in a municipal school in a town in the Cariri region of Paraíba. They live in a rural environment, where the main source of income is cattle raising, as well as cheese and milk production. We adopted a qualitative approach, characterized as participatory research, also incorporating elements of ethnographic research. Various methods were used for data collection, such as questionnaires, conversations with students, classroom observations, diagnostic activities, and didactic interventions. These tools were aimed at mapping the students' backgrounds, their cultural knowledge, and the mathematical knowledge applied in their daily routines. The data were organized into field diaries and tables, and the analysis was conducted based on theoretical categories and content analysis. As a result, a significant participation of students in the proposed activities was observed, which were based on dialogue, the appreciation of prior knowledge, and interaction, with a special focus on the application of mathematics in milk and cheese production. Inspired by Freirean principles, the activities addressed real-life situations, such as milk loss in cheese production and the low profitability of producers during certain periods. However, the results reveal that school content is still being presented disconnected from the students' daily experiences, as evidenced by their difficulty in applying concepts such as percentage in their daily routines.